ANALISIS EFEKTIVITAS PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA BANJARMASIN TAHUN 2019-2021 - Nur Auliah Rahmini; Muhammad Nordiansyah (Universitas Lambung Mangkurat, 2022)
The purpose of this study is to analyze the effectiveness and find out how big the percentage achieved by KPP Pratama Banjarmasin in tax revenue. The results of the research conducted in 2019-2021 before and after the reorganization occurred at the KPP Pratama Banjarmasin, there was an average value of the effectiveness ratio for Non-Oil and Gas PPh including very effective criteria, PPN and PPnBM including less effective criteria, PBB including very effective criteria, and Taxes Others include ineffective criteria